Age estimation by analysis of dental mineralization and its forensic contribution (Research, Society and Development, 2021)
Age is an important factor in the formation of the uniqueness of individuals. The procedure for assessing age in situations that cannot determine chronological age, especially in court cases, is mandatory. The literature presents different methods to estimate the age of individuals because civil and criminal majority at 18 years is a milestone in Brazil and other countries. Thus, age estimation through the analysis of dental mineralization stages is important, as it is rarely affected by exogenous or endogenous factors. This study evaluates different methods used to estimate age through dental mineralization and its forensic contribution. The following databases were used: PubMed, Medline, Scopus, Web of Science, and Google Scholar, using the descriptors "age estimation", "dental age estimation", and "forensic dentistry", both isolated and combined. It was verified the reliability of the analysis of dental mineralization stages for age estimation. Some of the methods used for this purpose have not been tested in Brazilian individuals. There are no up-to-date data on mineralization stages of permanent teeth for this population. Thus, current and specific data from the Brazilian population are required because the results to be obtained from new studies could benefit society, assisting the clarification of Justice in real-life situations.